Targeting Nucleolin in Lung Cancer: towards a personalized therapy - Fernandes, Ângela Filipa Valério (2016)
Thesis submitted to the Institute for Interdisciplinary Research of the University of Coimbra to apply for the degree of Doctor in Philosophy in the area of Experimental Biology and Biomedicine, specialization in Oncobiology.